2019
DOI: 10.1007/s00109-019-01800-1
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-coating of plastic surfaces prevents ventilator-associated pneumonia

Abstract: Ventilator-associated pneumonia (VAP) is a major cause of morbidity and mortality in critically ill patients. Here, we employed the broad antibacterial effects of sphingosine to prevent VAP by developing a novel method of coating surfaces of endotracheal tubes with sphingosine and sphingosine analogs. Sphingosine and phytosphingosine coatings of endotracheal tubes prevent adherence and mediate killing of Pseudomonas aeruginosa , Acinetobacter baumannii , an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…Overall, many recent studies have proved that sphingosine and some of its derivatives have antibacterial activity against a variety of species including, among others, P. aeruginosa , Acinetobacter baumannii , Escherichia coli , S. aureus and Streptococci species [ 42 , 44 , 46 , 47 , 49 , 50 , 51 ]. A sphingosine coating of endotracheal tubes has even recently been tested against P. aeruginosa , A. baumannii and S. aureus and it showed a great capacity to prevent bacteria adherence and protection from ventilator-associated pneumonia (VAP) in vivo [ 52 ]. A recent MoA study has reported that sphingosine causes the rapid permeabilization of the bacterial membrane of P. aeruginosa and S. aureus through the binding of sphingosine’s protonated nitrogen group with cardiolipin, a negatively charged membrane protein [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, many recent studies have proved that sphingosine and some of its derivatives have antibacterial activity against a variety of species including, among others, P. aeruginosa , Acinetobacter baumannii , Escherichia coli , S. aureus and Streptococci species [ 42 , 44 , 46 , 47 , 49 , 50 , 51 ]. A sphingosine coating of endotracheal tubes has even recently been tested against P. aeruginosa , A. baumannii and S. aureus and it showed a great capacity to prevent bacteria adherence and protection from ventilator-associated pneumonia (VAP) in vivo [ 52 ]. A recent MoA study has reported that sphingosine causes the rapid permeabilization of the bacterial membrane of P. aeruginosa and S. aureus through the binding of sphingosine’s protonated nitrogen group with cardiolipin, a negatively charged membrane protein [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanism of sphingosine's bactericidal effect has not yet been fully resolved in detail. It is known that micellar sphingosine kills many pathogens including Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Acinetobacter baumannii, Moraxella catarrhalis, Haemophilus influenzae, Burkholderia cepacia, Neisseria meningitides, and Neisseria gonorrhoeae [9,[29][30][31][32][33][34]. It is possible that sphingosine simply kills pathogens by its biophysical properties, which would also suggest that sphingosine's antimicrobial mechanism is not prone to the development of bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, these include early recognition of both carriers and infected patients ( Borer et al, 2012 ; Gorrie et al, 2017 ; Liu et al, 2019 ), and controlling the spread of pathogens with apparently still effective hand hygiene and disinfection of inanimate surfaces ( Kramer et al, 2006 ; Borer et al, 2012 ; Gorrie et al, 2017 ). Multiple studies also focus on novel approaches to prevent infections by coating endotracheal tubes and catheters with new antibacterial agents ( Caratto et al, 2017 ; Bjorling et al, 2018 ; Seitz et al, 2019 ). Such multifrontal measures to control K. pneumoniae is likely to be necessary for tempering both epidemic and non-epidemic strains.…”
Section: Discussionmentioning
confidence: 99%